ANALISIS PERUBAHAN TINGKAT KONSUMSI KELUARGA TENAGA KERJA INDONESIA (TKI) DI DESA SEPAYUNG KECAMATAN PLAMPANG - Karmeli, Elly; Safitri, Winda (Jurnal Ekonomi & Bisnis, 2024)
This study aims to know and analyze the consumption patterns of Indonesian Migrant Worker (TKI) families in Sepayung Village, Plampang Sub-district, Sumbawa District. The type of this study was descriptive study with a qualitative approach. The type of data used was qualitative data obtained directly from research informants. The informants who were the sources in this study were the families of Indonesian Migrant Workers (TKI) in Sepayung Village, Plampang Sub-district, Sumbawa District, totaling 27 people. The primary data to be studied in this study was collected using interview techniques. The data analysis technique in this study uses a qualitative data analysis model proposed by Miles and Huberman which consists of three stages carried out continuously, namely the data reduction stage, data presentation, and drawing conclusions/verification. The results of the study that there were consumptions changed of Indonesian workers families in Sepayung Village after becoming Indonesian migrants Workers. It can be seen from several changes as follows: families’ needs can be fulfilled and they can renovate their houses even they could built their houses, they could bough vehicles, they could sent their children to school and they had savings for the future. The factors that affected the consumption changed of Indonesian migrant workers families were are caused by income factors and the number of families members.